ISLAM DAN TRANSFORMASI SOSIAL DALAM PERSPEKTIF KUNTOWIJOYO - mulia, muji mulia (Universitas Islam Negery Ar-raniry, 2018)
Kuntowijoyo is one of the Indonesian Muslim thinkers who are very concerned in the field of social transformation while Islam must uphold the transcendental values of God Almighty. According to Kuntowijoyo, humans always make social changes and the QurÃ¢â¬â¢an must be become a paradigm and thought base. As a consequence of transformational religion, Islam makes its adherents as agents of social in social change. To carry out social transformation, the next agenda is to look for devices and tools to mobilize social dynamics. In that time, a prophetic social science that has an epistemological basis for the QurÃ¢â¬â¢an is needed. At the same time, the Quran must be made into a paradigm of thinking in understanding social reality. Kuntowijoyo believes that with the Quranic paradigm that offers theoretical values transformed into social reality, so with the Quran, Islam will be able to build civilization. Without being based on the Quranic paradigm, according to Kuntowijoyo, social change will lead to misleading change and civilization